Effective Communication Methods in Entrepreneurship Case Study of Qism Maqsof Banat STIBA Ar Raayah Sukabumi - Khatimah, Husnul; Trisnawati, Dewi; Rimayani, Diana; Nassila, Awfa (State Islamic Institute of Manado (IAIN) Manado, Indonesia, 2023)
This research aims to find out the effective communication methods of Qism Maqshaf Banat STIBA Ar Raayah in entrepreneurship. STIBA Ar Raayah students come from all over the archipelago from Sabang to Merauke which of course consists of various cultures, language dialects and distinctive communication characteristics in enriching the treasures of communication diversity in this pesantren-based college. This research uses a case study method with a qualitative approach supported by interviews, observation, and documentation. The results showed that to achieve effective internal communication, Qism Maqshaf goes through a series of processes, namely by conducting research on the needs and desires of female students and then in a traditional way they spread product reviews, as well as evaluating and providing feedback to suppliers. Qism Maqshaf members always provide the best service for prospective buyers in accordance with the vision and mission of business communication, such as by trying to understand the cultural characters and language dialects of each student who is a customer. Communication that is put forward in muamalah here is persuasive communication, which is to change or influence a person's attitude or behavior so that it acts in accordance with what is expected by the communicator.